Lichenoid drug eruption induced by chlordiazepoxide - Osamah M Alkhuzaim (Wolters Kluwer Medknow Publications, 2022)
Lichenoid drug reaction is a cutaneous drug eruption due to a Type IV delayed hypersensitivity reaction. It usually occurs months to years following the intake of the drug and is characterized by purple, flat, polygonal papules that spread symmetrically and diffusely across the body. We report the case of a 26-year-old female, who was on chlordiazepoxide for the treatment of insomnia, and presented with multiple, annular, purple, scaly, itchy plaques over her breasts. The eruption progressed to involve the thighs and buccal mucosa and did not respond to topical antifungals. Skin biopsy revealed lichenoid lymphocytic infiltrate consistent with lichen planus. After discontinuation of chlordiazepoxide, her skin eruption significantly improved within 3 months. To our knowledge, this is the first case report of a patient who developed a lichenoid drug reaction to chlordiazepoxide.